2020
DOI: 10.5860/crln.81.7.322
|View full text |Cite
|
Sign up to set email alerts
|

Empty shelves: How your academic library can address food insecurity

Abstract: Researchers have only recently begun looking at food insecurity on college campuses. Food insecurity is characterized by the U.S. Department of Agriculture (USDA) as limited or uncertain access to nutritionally adequate and safe foods or the ability to acquire acceptable foods in socially acceptable ways due to limited financial resources. Harmony Reppond illustrates this point when writing, “food insecurity for college students can mean running out of food between paychecks, attending campus events in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Academic libraries have lagged behind their public library peers in this regard. While many campuses have food pantries, academic libraries' involvement with them has thus far been relatively limited (Wood 2020). It should be noted that food banks are usually large facilities where food is stored and distributed to smaller entities, while a food pantry is more localized, acting similarly to a grocery store (Martin, Xu, and Schwartz 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Academic libraries have lagged behind their public library peers in this regard. While many campuses have food pantries, academic libraries' involvement with them has thus far been relatively limited (Wood 2020). It should be noted that food banks are usually large facilities where food is stored and distributed to smaller entities, while a food pantry is more localized, acting similarly to a grocery store (Martin, Xu, and Schwartz 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A report released by the US Government Accountability Office in late 2018 reviewed 22 applicable studies related to food insecurity and found that more than 30 percent of college students face food insecurity at some point in their college career amid the rising costs of higher education (US Government Accountability Office 2018). Student food insecurity is experienced at higher rates by traditionally underrepresented groups, "including first-generation college students, Black and Indigenous people, single parents, people with disabilities, nonbinary and trans-identifying individuals, former foster youth, and those who are presently unhoused or at risk of homelessness" (Wood 2020).…”
mentioning
confidence: 99%
“…In the circumstance that awareness exists, stigma is also a known barrier to accessing resources (1,2,4,43) . Some campuses have intentionally aimed to mitigate stigma by centralising their food pantries in visible locations on campus (35,46) ; however, more needs to be done to ensure these campus programmes are socially acceptable by marginalised students. In general, efforts should include education to students and other campus stakeholders on the impact of unmet basic needs, such as access to safe, affordable and healthy food, on academic success and health outcomes (4) .…”
Section: Individual Factorsmentioning
confidence: 99%